2013
DOI: 10.1115/1.4025944
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Approach for Condition Monitoring of Reciprocating Compressor Valves

Abstract: This paper focuses on condition-monitoring of three different valve failure modes common in reciprocating compressors. They are missing valve poppets, valve spring fatigue, and valve seat wear. Eirst, a targeted instrumentation study is performed on a Dresser-Rand ESH-l industrial reciprocating compressor to investigate detection methods for these failures. This is followed by the development of a novel health classification methodology based on frequency analysis and Bayes theorem. The method is shown to succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Guerra and Kolodziej [41] proposed a data-driven approach for condition monitoring of RC valves. An FFT was applied to the pressure wave measured in the environment around the discharge valve, and then the FFT values were grouped into several frequency bins.…”
Section: Fault Diagnosis Based On Pressures Measured In Other Volumesmentioning
confidence: 99%
“…Guerra and Kolodziej [41] proposed a data-driven approach for condition monitoring of RC valves. An FFT was applied to the pressure wave measured in the environment around the discharge valve, and then the FFT values were grouped into several frequency bins.…”
Section: Fault Diagnosis Based On Pressures Measured In Other Volumesmentioning
confidence: 99%
“…In 2013, using the compressor in this work at the RIT Compression Test Cell, (Guerra & Kolodziej, 2014) developed a mechanical-thermodynamic model of the compressor and investigated health monitoring of discharge valves using P-V diagrams, dynamic pressure measurements, and frequency domain analysis. Later, (Kolodziej & Trout, 2018) extended this work into the time-frequency domain using image processing methods, and most recently (Scott & Kolodziej, 2020) investigated fault isolation of valve health across all manifolds, inlet and outlet, using a novelty detection SVM.…”
Section: Introductionmentioning
confidence: 99%
“…Several research works applying PHM technologies in reciprocating compressors have been reported. A research concerning the condition monitoring of the valves by using analytical and data-driven technologies is reported in [10]. The research analyzes different valve failure modes, and also investigates the type of sensors useful for detecting such faults.…”
Section: Introductionmentioning
confidence: 99%